Planificación estratégica y desarrollo territorial - Chiarella Quinhoes, Roberto (2005)
This paper focuses on the strategic planning method linked to the territory' s sustainable development as it is currendy being proposed by various organisms involved in public policies in Peru. lt is aimed to discuss the methodology in terms of its validity as a new theoretical paradigm. lts ultimare goal is to bring about a new comprehension of the strategic planning process within the present competitive framework -among districts, provinces, regions, etc.- featured by factors such as human resources assessment, expressive technological investments and emphasis on inter-connectivity, among others.The paper starts by revising the strategic planning model genesis within the publicinitiative sector and its relationship with the attraction of privare investments at local scale. The percourse which  links one point  to the other goes through  both  the perspective of economists and administrators and the vision of prominent planners. lt ends up by showing the possibilities of a new prospect in the strategic planning of development at local scale, as well as existing doubts regarding the model: firstly, if we lack adequate information in reference to the objective capacities of our closest competitors, we will hardly be able to elaborare competitive strategies favorable to us in a specific environment; secondly, we consider that, in the current context of our country, the goals  in the territory development  process  must be guidelined  by employment and income generation for local population and this, without doubt, relies on systematic planning of investment attraction; and finally, we accept that strategic planning may constitute a tool that will enable to consolidare the decentralization and territorial integration processes.